Do related party transactions affect earnings quality? Evidence from East Asia. Issue 1 (13th January 2020) - Rahmat, Mohd Mohid; Muniandy, Balachandran; Ahmed, Kamran
Abstract : Purpose: The purpose of this paper is to examine the effect of related party transactions (RPTs) and types of RPTs (complex, simple and loan) on earnings quality in four East Asian countries: Hong Kong, Malaysia, Singapore and Thailand. Design/methodology/approach: RPTs and types of RPTs are measured using two approaches, magnitude and abnormal (magnitude change). Earnings quality is measured using proxies for accrual earnings management and identified as discretionary accruals (DAC) and performance matched discretional accruals (PMDAC). Findings: The results suggest that firms in these countries experience poor earnings quality when they are engaged in RPT. The effect of RPT-simple on earnings quality is more severe than RPT-complex. However, the presence of higher investor protection and stricter enforcement of regulations in countries like Singapore and Hong Kong reduce the negative impact of RPTs on earnings quality. Research limitations/implications: The results support the argument that the presence of controlling shareholders in East Asia is likely to lead to engagement with RPTs, which will increase the likelihood of firms' earnings manipulation via DAC. This study has two limitations. It only focuses on Hong Kong, Malaysia, Singapore and Thailand, and the results may not be generalizable to other countries. Second, this study only measures the magnitude and abnormal RPTs based on the disclosures available in annual reports. Originality/value: This paper contributes to the literature by examining the effect of RPTs and types of RPTs on earnings quality in four selected East Asian countries.